2020
DOI: 10.1002/jdd.12485
|View full text |Cite
|
Sign up to set email alerts
|

How US dental schools can better prepare their students to perform operative procedures

Abstract: Objective The aim of this study was to characterize the curricular and supplemental resources used by dental students during their operative dentistry course, survey students’ perception of each resource's “helpfulness,” and assess students’ perceptions of preparedness to perform operative dental procedures in clinical settings. Methods American Student Dental Association delegates at all accredited dental education programs in the United States were asked to forward an email to students enrolled at their resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…This finding was corroborated by a national study published by He et al. in 2021, which found that YouTube was the most common supplemental resource utilized by dental students (80%) 3 . Further, in the He et al.…”
Section: Introductionmentioning
confidence: 52%
See 4 more Smart Citations
“…This finding was corroborated by a national study published by He et al. in 2021, which found that YouTube was the most common supplemental resource utilized by dental students (80%) 3 . Further, in the He et al.…”
Section: Introductionmentioning
confidence: 52%
“…2 This finding was corroborated by a national study published by He et al in 2021, which found that YouTube was the most common supplemental resource utilized by dental students (80%). 3 Further, in the He et al study, YouTube was ranked as the second most helpful of all presented curricular and supplemental resources. 3 In the study by Burns et al, dental students were asked about which types of dental procedures they prepare for using YouTube: Endodontics was one of the most frequently selected disciplines across all of the dental schools surveyed.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations